DOI: 10.1039/9781782620037-00072
|View full text |Cite
|
Sign up to set email alerts
|

Chapter 3. Novel carbon materials modified with heteroatoms as metal-free catalyst and metal catalyst support

Abstract: The discovery of novel carbon materials (carbon nanotubes, graphene) has extended the window for the application of carbon materials as catalyst and catalyst support. The electronic conductivity, ordered structure and absence of microporosity are some favourable properties compared to disordered conventional carbon materials. The ordered nature of these materials allows the precise functionalization with heteroatoms which have shown good perspectives as metal free catalyst. Herein, the more recent catalytic ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 139 publications
(183 reference statements)
1
11
0
Order By: Relevance
“…A blank experiment showed that the reaction of CyO with H 2 O 2 in the presence of POM-free N-CNTs in MeCN could give a conversion of 50%, but no epoxide was found among the reaction products (Table 2, entry 5). This result agrees with the previously reported results on N-CNT activity in different oxidation reactions due to the presence of nitrogen species (García-Bordejé et al, 2014).…”
Section: Catalytic Performance Of Pw 4 /N-cnts and Pw 4 /Cnts In Alkesupporting
confidence: 94%
See 2 more Smart Citations
“…A blank experiment showed that the reaction of CyO with H 2 O 2 in the presence of POM-free N-CNTs in MeCN could give a conversion of 50%, but no epoxide was found among the reaction products (Table 2, entry 5). This result agrees with the previously reported results on N-CNT activity in different oxidation reactions due to the presence of nitrogen species (García-Bordejé et al, 2014).…”
Section: Catalytic Performance Of Pw 4 /N-cnts and Pw 4 /Cnts In Alkesupporting
confidence: 94%
“…Doping of CNMs by nitrogen (N-CNMs) by a catalytic growth route leads to the incorporation of N atoms into the carbon matrix throughout the volume, including the surface layer (García-Bordejé et al, 2014). The formation of different surface N species may diversify approaches to immobilization of catalytically active species and affect specific surface properties of heterogeneous catalysts (García-Bordejé et al, 2014;Arrigo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now believed that the doping of heteroatoms into carbon frameworks (e. g., nitrogen, sulfur, phosphorus, and boron) is an excellent strategy that can significantly influence the interactions between support and metal by precision tuning of electronic and chemical properties and surface structures of supports and ultimately increase the efficiency and selectivity of the designed catalytic systems [24] . Also, this efficient and straightforward method can lead to a decrease in the amount of metal necessary for a catalytic reaction, particularly in the case of costly noble metals [25] …”
Section: Introductionmentioning
confidence: 99%
“…In comparison with oxygen [2,3,7,[48][49][50][51][52][53][54][55] and nitrogen [7,14,15,53,[56][57][58][59][60][61][62][63][64][65][66] heteroatoms, phosphorus has received much less attention. This is reflected in only some brief mention to phosphorus-containing carbons in reviews on much broader subjects [17,49,53,[67][68][69][70][71] and incomplete reviews restricted to the effect of phosphorus on carbon adsorbents [72,73]. Only the property of phosphorus heteroatom to inhibit oxidation of carbon materials was investigated in depth due to its practical importance for the aerospace industry [68].…”
Section: Introductionmentioning
confidence: 99%